SMALL GUT VOLVULUS, A RARE TWIST, IN THE SETTING OF AN EVEN RARER ENTITY; MULTIPLE GIANT JEJUNO ILEAL DIVERTICULA - Khan, Ayesha; Khan, Faheem; Rafique, Kashif; Khan, Sarwar; Majid, Anam; Khan, Khalid; Ullah, Asad (Journal of Ayub Medical College Abbottabad, 2017)
Small gut volvulus with multiple Jejuno-ileal diverticulosis is an unusual pathology of the small intestine with a scarce number of cases reported so far. It usually goes unnoticed because it is often asymptomatic but complications like diverticulitis, perforation, bleeding or intestinal obstruction can occur in 10-30% of the cases. Mechanical obstruction, if it occurs, can be caused by adhesions or stenosis due to diverticulitis, intussusception at the site of the diverticulum and volvulus of the segment containing the diverticula. Acute volvulus of the small bowel is a serious abdominal emergency that poses a difficulty in diagnosis and delayed operative intervention can lead to dire consequences. We herein report the case of a 42-year-old man presented at the emergency department with acute abdominal pain, absolute constipation and vomiting. Preoperative investigations followed by laparotomy revealed small gut volvulus and multiple giant jejunal and ileal diverticula. Keywords: Small gut volvulus; small intestinal volvulus; diverticula; volvulus, jejunoileal diverticulosis, intestinal obstruction, exploratory laparotomy, acute abdomen